Manifestasi Perdarahan pada Pasien Demam Berdarah Dengue yang Dirawat di Ruang Rawat Inap Anak RSUP Sanglah Denpasar - Astika, Nyoman Dinar; Lingga Utama, I Made Gede Dwi (E-Jurnal Medika Udayana, 2017)
Bleeding is one of clinical manifestations usually found in dengue hemorrhagic fever patients. Bleeding can be manifested in various type, it can be seen through the skin, as mucosal bleeding, or as gastrointestinal bleeding. The aim of this study is to know which bleeding manifestation that usually found in patient with dengue hemorrhagic fever that treated in the inpatient child Sanglah General Hospital Denpasar. This study was a descriptive study with a cross-sectional and non-experimental design which used secondary data from medical record of dengue hemorrhagic patients in Sanglah General Hospital Denpasar. Bleeding manifestations found in samples can be seen as a positive result of tourniquet test and petechiae in 24 cases (48%) and 34 cases (68%) respectively, epistaksis in 7 cases (14%), gingival bleeding in 5 cases (10%), hematemesis in 1 case (2%), and melena in 6 cases (12%). During January 2013 until October 2014, there are 50 dengue hemorrhagic fever patients that show bleeding manifestation. It is equal for both 5 boys and 25 girls, with greatest incidence is in age group of 5 years, total 8 cases (16%). The commonest bleeding manifestation found is petechiae, total 34 cases (68%). Keywords: dengue fever, characteristic